IoT task management system using control board - Changsu Kim; Youngkuk Kim; Hoekyung Jung (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Recently, Internet of Things (IoT) has been providing services that increase convenience for users by connecting objects to a network. As a result, the number of users and smart devices utilizing IoT is also increasing. So, the existing system has a problem that when a variety of devices are added, a bottleneck or an overload of the server occurs, because of structure of the system. In this paper, we propose IoT task management system using control board to solve these problems. The server performs only simple communication and analysis, and the management of tasks such as remote control is carried out using the control board. Also, it analyzes the user's remote control command and recommends to users the most used equipment. Through this, it is possible to reduce the data throughput and traffic of the server and to provide the service with increased convenience and accuracy of operation.